2017
DOI: 10.1186/s12885-016-3024-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative changes in osteopontin and TGFβ1 plasma levels and their prognostic impact for radiotherapy in head and neck cancer

Abstract: BackgroundIn head and neck cancer little is known about the kinetics of osteopontin (OPN) expression after tumor resection. In this study we evaluated the time course of OPN plasma levels before and after surgery.MethodsBetween 2011 and 2013 41 consecutive head and neck cancer patients were enrolled in a prospective study (group A). At different time points plasma samples were collected: T0) before, T1) 1 day, T2) 1 week and T3) 4 weeks after surgery. Osteopontin and TGFβ1 plasma concentrations were measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Moreover, high osteopontin level had a negative impact on disease‐free survival. In a study conducted by Polat et al, 24 cases with head and neck cancer had higher osteopontin levels compared to the control group, in agreement with our study. In addition, they observed that patients that were suitable for surgery, in terms of survival, and those with a serum osteopontin level below the median value were advantageous in terms of survival.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, high osteopontin level had a negative impact on disease‐free survival. In a study conducted by Polat et al, 24 cases with head and neck cancer had higher osteopontin levels compared to the control group, in agreement with our study. In addition, they observed that patients that were suitable for surgery, in terms of survival, and those with a serum osteopontin level below the median value were advantageous in terms of survival.…”
Section: Discussionsupporting
confidence: 93%
“…24 It was also proposed that osteopontin had a prognostic role in terms of survival in patients that are not suitable for surgery or in those that underwent surgery and adjuvant radiotherapy. 24 In another study that included 578 patients with stage 3 to 4 head and neck cancer, plasma osteopontin levels intriguingly did not have any prognostic effects on overall and diseasefree survivals. 25 In contrast, Li et al 21 suggested that patients with both tissue expression and high plasma levels of osteopontin had shorter survival and were more likely to have distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, we are developing a test to evaluate the circulating levels of OPN in patients with lung cancer in order to establish if plasma levels of OPN can also be a prognostic/diagnostic factor for these patients and hopefully to develop a clinically deliverable test in the regards. Indeed, circulating OPN in patients with breast cancer (27), liver cancer (28), colorectal cancer (29), squamous cell carcinoma (30), ovarian cancer (31) and in non-cancer related medical conditions such as systemic lupus erythematomatus (32) and in autoimmune encephalomyelitis (33) have been reported to have clinical relevance. In lung cancer, this has also been tested, plasma OPN prior and after radiation therapy has been suggested to be an additional prognostic marker (34).…”
Section: Figure 4 Effect Of Opn and ανβ3 Integrin On Adhesion Of A54mentioning
confidence: 99%